Digital Transformation as a Structural Enabler of Zero-Carbon Mobility: A Practice Perspective from Emerging Economies - Astri Rumondang Banjarnahor; Juliater Simarmata (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
This research aims to explain how digital transformation plays a role as a structural enabler in accelerating the transition to zero-carbon mobility. This study examines the real-world practices of digital technology adoption in the sustainable transportation sector by highlighting how industry actors are navigating the challenges of decarbonization, governance, and cross-sector collaboration. This study uses a practice perspective approach, which emphasizes analysis of the empirical practices of industry players, regulators, and digital service providers. Two main case studies—Gojek and Blue Bird Group—were selected to illustrate the strategic implementation of digitalization through route optimization, fleet electrification, predictive maintenance systems, and the use of real-time telematics. The analysis was carried out qualitatively based on secondary data triangulation and literature synthesis. The results show that digitalization significantly reduces carbon intensity and improves operational efficiency, but is still faced with obstacles in the form of infrastructure inequality, initial investment costs, and digital literacy gaps. The success of the green mobility transition is proven to depend on the synergy between technological innovation, digital governance, and multi-stakeholder collaboration. These findings provide strategic implications for policymakers and industry players to design digital policies and ecosystems that are inclusive, data-driven, and aligned with the Net Zero Emission 2060 agenda. The study also expands the literature by showing how digitalization integration can strengthen sustainability capabilities in the context of emerging economies